G439(P) Wellcome home – the work of shelter, a charitable organisation in facilitating the discharge of children with medical complexities (cmic). (12th March 2018) - Bassett, E; Shanahan, R; Allen, N
Abstract : Aims: Our CMiC Team coordinate compassionate care and facilitate a safe discharge for patients with complex medical conditions±social needs (CMiC criteria), whilst linking together patient-focused working for health and social care services. WELLcome Home aimed to improve the quality of the long journey home. Methods: Shelter established a pilot 7 month housing support service (WELLcome Home) for CMiC families. An onsite Shelter support worker guides families through the social housing pathway, raises the profile where housing prevents discharge, and contributes to CMiC multidisciplinary team meetings, bridging the gap between Health and Social Care. Results: Service-user evaluation questionnaires provided qualitative data across seven modalities (table 1). Conclusion: The WELLcome home project demonstrated positive qualitative outcomes across all modalities assessed. Between January-June 2017, housing provided discharge barriers for 15 long-stay patients. Additional length of stay due to housing need exceeds 1000 bed-days for this patient subgroup. Funding for Shelter at our Hospital is secured for 5 years. Collaborative, imaginative working is vital to continue supporting our most vulnerable and complex families.